Expansion of metabolically labelled endocytic organelles and cytoskeletal cell structures in Giardia lamblia using optimised U-ExM protocols - Clirim Jetishi; Erina A Balmer; Bianca M Berger; Carmen Faso; Torsten Ochsenreiter (Microbial Cell)
Understanding cellular ultrastructure is tightly bound to microscopic resolution and the ability to identify individual components at that resolution. Expansion microscopy has revolutionised this topic. Here we present and compare two protocols of ultrastructure expansion microscopy that allow for 4.5-fold mostly isotropic expansion and the use of antibodies, metabolic labelling, and DNA stains to demarcate individual regions such as the endoplasmic reticulum, the nuclei, the peripheral endocytic compartments as well as the ventral disc and the cytoskeleton in Giardia lamblia. We present an optimised, shortened, and modular protocol that can be swiftly adjusted to the investigators needs in this important protozoan model organism.